Effectiveness of an evidence-based care pathway to improve mobility and participation in older patients with vertigo and balance disorders in primary care (MobilE-PHY2): study protocol for a multicentre cluster-randomised controlled trial - Horstmannshoff, Caren; Skudlik, Stefanie; Petermann, Jenny; Kiesel, Theresia; Döringer, Tobias; Crispin, Alexander; Hermsdörfer, Joachim; Köberlein-Neu, Juliane; Jahn, Klaus; Schädler, Stefan; Bauer, Petra; Voigt, Karen; et al. (Trials, 2023)
Vertigo, dizziness or balance disorders (VDB) are common leading symptoms in older people, which can have a negative impact on their mobility and participation in daily live, yet, diagnosis is challenging and specific treatment is often insufficient. An evidence-based, multidisciplinary care pathway (CPW) in primary care was developed and pilot tested in a previous study. The aim of the present study is to evaluate the effectiveness and safety of the CPW in terms of improving mobility and participation in community-dwelling older people with VDB in primary care.